BI-RADS CLASSIFICATION FOR BREAST ULTRASOUND : A REVIEW - Abdulloh, Arizal; Ni'mah, Ana Qomariyatun (Transpublika Publisher, 2023)
Breast cancer is the most common form of cancer in women worldwide. According to statistics from GLOBOCAN 2020, 1.2 million women are diagnosed with breast cancer each year, and 410,000 (35%) will die from this disease. Breast cancer is the most prevalent type of cancer among women in Indonesia, accounting for 30.8% of all female cancer cases in 2020 and causing 20.4% of female cancer-related deaths in the same year. Breast cancer screening plays a vital role in reducing deaths caused by breast cancer. Various breast cancer imaging techniques have been introduced for diagnosing breast cancer, such as Magnetic Resonance (MR) mammography, Ultrasound, Elastography, Mammography, and Automated Breast Ultrasound (ABUS). Ultrasound (US) and mammography are the two most important modalities for breast imaging. In younger women under the age of 35, ultrasound is the primary tool used to investigate breast problems. Even in the older age group, ultrasound plays a crucial role in breast imaging, particularly for the assessment of mass lesions. Breast ultrasound can be used for both screening and diagnostic purposes. Ultrasound evaluates breast tissue without the use of ionizing radiation or the injection of contrast material and is affordable, readily available, and well-tolerated by patients. The American College of Radiology (ACR) proposed the Breast Imaging Reporting and Data System (BI-RADS) to standardize the characterization of sonographic breast lesions according to five criteria categories: mass shape, orientation, margin, echo pattern, and posterior features.